Accuracy of Point‐of‐care Ultrasonography for Diagnosing Acute Appendicitis: A Systematic Review and Meta‐analysis. (21st August 2017) - Matthew Fields, J.; Davis, Joshua; Alsup, Carl; Bates, Amanda; Au, Arthur; Adhikari, Srikar; Farrell, Isaac
Abstract: Background: The use of ultrasonography (US) to diagnose appendicitis is well established. More recently, point‐of‐care ultrasonography (POCUS) has also been studied for the diagnosis of appendicitis, which may also prove a valuable diagnostic tool. The purpose of this study was through systematic review and meta‐analysis to identify the test characteristics of POCUS, specifically US performed by a nonradiologist physician, in accurately diagnosing acute appendicitis in patients of any age. Methods: We conducted a thorough and systematic literature search of English language articles published on point‐of‐care, physician‐performed transabdominal US used for the diagnosis of acute appendicitis from 1980 to May, 2015 using OVID MEDLINE In‐Process & Other Non‐indexed Citations and Scopus. Studies were selected and subsequently independently abstracted by two trained reviewers. A random‐effects pooled analysis was used to construct a hierarchical summary receiver operator characteristic curve, and a meta‐regression was performed. Quality of studies was assessed using the QUADAS‐2 tool. Results: Our search yielded 5, 792 unique studies and we included 21 of these in our final review. Prevalence of disease in this study was 29.8%, (range = 6.4%–75.4%). The sensitivity and specificity for POCUS in diagnosing appendicitis were 91% (95% confidence interval [CI] = 83%–96%) and 97% (95% CI = 91%–99%), respectively. The positive and negative predictive values were 91 and 94%, respectively. Studies performed by emergency physicians had slightly lower test characteristics (sensitivity = 80%, specificity = 92%). There was significant heterogeneity between studies (I 2 = 99%, 95% CI = 99%–100%) and the quality of the reported studies was moderate, mostly due to unclear reporting of blinding of physicians and timing of scanning and patient enrollment. Several of the studies were performed by a single operator, and the education and training of the operators were variably reported. Conclusion: Point‐of‐care US has relatively high sensitivity and specificity for diagnosing acute appendicitis, although the data presented are limited by the quality of the original studies and large CIs. In the hands of an experienced operator, POCUS is an appropriate initial imaging modality for diagnosing appendicitis. Based on our results, it is premature to utilize POCUS as a stand‐alone test or to rule out appendicitis.